Combined anomalies of axial skeleton - O. A. Kaplunova; E. V. Chaplygina; O. P. Suhanova; N. A. Fomina-Chertousova; I. M. Blinov; B. M. Kalashaov (Медицинский вестник Юга России, 2019)
Detection of the combined anomalies of the axial skeleton, including anomalies of the craniovertebral junction, cervical spine and ribs, is rare, and the differential diagnosis of such anomalies is a difficult task. Clinical cases of combined congenital malformations of the craniovertebral junction, cervical spine and ribs are described. Two clinical cases confirm the appearance of the first complaints and neurological syndromes in patients with combined anomalies of the axial skeleton at the age of 20-40 years after minor traumatic injuries. In the third case, there is no correspondence between the severity of radiological changes and clinical manifestations, when radiological findings were regarded as accidental.